Polypyrrole nanoparticles for tunable, pH-sensitive and sustained drug release. Issue 21 (1st May 2015) - Samanta, Devleena; Meiser, Jana L.; Zare, Richard N.
Abstract : Charged drug molecules from nanoparticles are released by changing the pH of the surroundings and fine-tuned by adding appropriate amphiphiles. Abstract : We report the development of a generalized pH-sensitive drug delivery system that can release any charged drug preferentially at the pH range of interest. Our system is based on polypyrrole nanoparticles (PPy NPs), synthesized via a simple one-step microemulsion technique. These nanoparticles are highly monodisperse, stable in solution over the period of a month, and have good drug loading capacity (∼15 wt%). We show that PPy NPs can be tuned to release drugs at both acidic and basic pH by varying the pH, the charge of the drug, as well as by adding small amounts of charged amphiphiles. Moreover, these NPs may be delivered locally by immobilizing them in a hydrogel. Our studies show encapsulation within a calcium alginate hydrogel results in sustained release of the incorporated drug for more than 21 days. Such a nanoparticle-hydrogel composite drug delivery system is promising for treatment of long-lasting conditions such as cancer and chronic pain which require controlled, localized, and sustained drug release.